A review of the regulatory norms of work in Brazil within the context of biosafety in dentistry - Soares, A. F.; Gomes de Moraes, G. A. [UNESP]; Menezes, M. L. [UNESP] (Taylor & Francis, 2015)
Biosecurity in dentistry is a subject on which there is little discussion in the literature, and in general, the articles found are addressed to dental surgeons and undergraduates. Therefore, it was necessary to conduct a study concerning the work of the dental school faculty member, by inserting it into the context of biosafety, as a professional class subject to all types of occupational risks, thus deserving all the labor and social security rights that Brazilian legislation offers. Occupational infectious diseases such as hepatitis B and C and AIDS are cause for concern among health professionals. In this research, it was determined that dentistry professionals, in general, are exposed to a number of environmental risks defined in Ordinance 3.214/78, in accordance with the regulatory standards of the Ministry of Labor and Employment. Therefore they deserve to receive the additional protection that the law provides, in these specific cases.